Depression and anxiety in people deprived of their freedom - Mejia Rodriguez, Ulises Papillón (2023)
Depression and anxiety are two of the most common mental disorders in the general population, and are most associated with an increased risk of committing suicide. Specifically, the reported prevalence of depression varies from 8 to 12 %, and anxiety reaches a prevalence of 4,3 to 5,9 %, both of which are more common in women. Mental disorders are more common in prisoners than in the general population. Approximately 1 in 7 prisoners has a treatable mental illness. The prevalence of serious mental illnesses among incarcerated adult men and women is 14,5 % and 31 % respectively, considerably higher than that found in the general population, which is 4.1% (women: 4,9% and men 3,2 %.